On the effect of the built environment and preferences on non-work travel: Evidence from Japan - Parady, Giancarlos Troncoso; Chikaraishi, Makoto; Takami, Kiyoshi; Ohmori, Nobuaki; Harata, Noboru (European Journal of Transport and Infrastructure Research, 2015)
This study uses data from the 4th Nationwide Person Trip Survey to analyse the relation between the built environment, modal access preference at residential location and travel behaviour in Japan. By estimating random parameter count models, significant statistical associations were found between the built environment and preferences with non-work trip frequency by mode. Furthermore the effect of population density, car ownership and some access preference traits were found to be heterogeneous for some modes. Since most of the recent literature has focused largely on North-American and European cities, this study contributes to the existing body of literature by examining the role of the built environment and individual preferences on travel behaviour in the context of Japanese cities, and sheds some light on existing heterogeneity in the effects of some factors related to travel behaviour.